Unilateral Trigeminal Sensory Neuropathy with Sjögren's Syndrome with Liver and Renal Impairment - Kana Ozasa; Noboru Noma; Jumi Nakata; Yoshiki Imamura (MDPI AG, 2021)
Liver and renal involvement is a rare event in Sjögren's syndrome. Sjögren's syndrome is characterized by the progressive immune-mediated destruction of epithelial tissues of the salivary and lacrimal glands. Sensory ganglionitis, accompanied by T-cell invasion, occurs in patients with Sjögren's syndrome, resulting in sensory neuropathy of the face or limbs. Patients are assessed by quantitative sensory testing. A 76-year-old woman presented with numbness of her left face and was subsequently diagnosed with Sjögren's syndrome and primary biliary cirrhosis, and was found to have renal failure. Detection of her serum anti-Ro/SSA antibody was strongly positive. Shirmer's test or a salivary volume in the gum test also showed positive results. Her somatosensory disturbance severity was higher in the trigeminal area than in the forearm, suggesting that the trigeminal nerve is more susceptible than other parts of the nervous system in patients with Sjögren's syndrome and primary biliary cirrhosis. A simple sensory test could be performed during regular check-ups, as sensory deficits might develop after patients are diagnosed with Sjögren's syndrome and primary biliary cirrhosis.